Applying the INQUA scale to the Sofades 1954, Central Greece, earthquake - Papathanassiou, G.; Valkaniotis, S.; Pavlides, S. (Bulletin of the Geological Society of Greece, 2007)
Macroseismic intensity scales are used in order to measure the size of an earthquake using the impact of the ground shaking on humans, man made environment and nature. The INQUA scale is a new scale based solely on the earthquake-induced ground deformations, proposed by the INQUA Subcommission on Paleoseismicity. This scale is applied to the Sofades 1954 earthquake in order to test its accuracy and reliability. From the comparison among the evaluated intensities based on MM scale with the degrees of INQUA intensity at several locations, we conclude that, in case of earthquakes which triggered remarkable geological effects, these intensity values are about the same. Nonetheless, the use of INQUA scale is suggested in combination with the existing ones, as an assessing tool of the intensity based only on geological effects